2001
DOI: 10.1136/heart.86.4.376
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of left ventricular diastolic function and association with heart rate variability after a first acute myocardial infarction

Abstract: Objective-To study the prognostic value of left ventricular (LV) diastolic function and its relation with autonomic balance expressed by heart rate variability (HRV) in patients after a first acute myocardial infarction. Design-The study population consisted of 64 consecutive patients with first acute myocardial infarction and 31 control subjects. Long and short term HRV indices were evaluated by 24 hour Holter monitoring, and LV systolic and diastolic function were assessed by two dimensional and Doppler echo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 31 publications
3
19
0
3
Order By: Relevance
“…Impaired relaxation was defined as an E/A < 1 [19]. As previously defined [20,21] , when E/A was > 1 but < 2 associated with DT (deceleration time of the E wave) < 140 ms or when E/ A > 2 the pattern of LV filling was defined as restrictive. A non-restrictive pattern of LV filling was defined by an E/ A < 1 or by E/A between 1 and 2 associated with DT > 140 ms. Isovolumic relaxation time (IVRT) was also measured as the time from the end of the A wave to the beginning of the aortic Doppler ultrasound wave.…”
Section: Methodsmentioning
confidence: 99%
“…Impaired relaxation was defined as an E/A < 1 [19]. As previously defined [20,21] , when E/A was > 1 but < 2 associated with DT (deceleration time of the E wave) < 140 ms or when E/ A > 2 the pattern of LV filling was defined as restrictive. A non-restrictive pattern of LV filling was defined by an E/ A < 1 or by E/A between 1 and 2 associated with DT > 140 ms. Isovolumic relaxation time (IVRT) was also measured as the time from the end of the A wave to the beginning of the aortic Doppler ultrasound wave.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to systolic function, diastolic function has received little attention in humans suffering from severe aortic regurgitation 52,53 . However, it has been suggested that abnormalities in diastolic function may influence the symptomatic status as well as the prognosis of subjects with severe aortic regurgitation as in other cardiac diseases such as myocardial infarction, congestive heart failure, diabetes and hypertension [54][55][56][57][58][59] . The occurrence of left ventricular filling abnormalities in our animals therefore deserves further attention and investigation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The clinical course of patients with acute anterior myocardial infarction (AMI) is related to the degree of left ventricular functional impairment. [4][5][6] Previous studies assessing TDE velocities of different mitral annular corners and myocardial segments in acute myocardial infarctions demonstrated the alterations in tissue velocities that are not limited to the infarct-related regions but also involve remote areas in the left ventricle. 7,8) The objective of the present study was to investigate whether relatively preserved systolic and diastolic performances, which are traditionally assessed with the ejection fraction (EF) and deceleration time of early diastolic filling (DT), could be predicted by some parameters obtained from the TDE profiles of septal, lateral, anterior, and inferior mitral annulus corners in patients suffering a first acute AMI.…”
Section: Discussionmentioning
confidence: 99%